Sanitation Behavior and Risk of Stunting: Understanding the Discourse of a Public Service Announcement - Liem, Silva; Marta, Rustono Farady; Panggabean, Hana (Universitas Semarang, 2019)
District Health Office of North Lombok Regency is developed a Public Service Announcement (PSA) to dealing with high stunting prevalence, by inform people about poor sanitation behavior and stunting. Using SaniFOAM framework, this study aimed to critically analyzed the sanitation behavior, its setting, narratives, images, conversations conveyed by the PSA and their intertextuality with socio-cultural background of the rural society, to see if it s an effective communication media in advocating public to stop open defecation. Fairclough s Critical Discourse Analysis used to identify what sanitation behavior to change; social norms including potential sanctions or enforcement leading to behavior change; required knowledge, and sources of social support to adopting healthier behavior; and to realize the individual and community attitudes, and values as drivers for the change. The result indicated handwashing was not reminded; believing in shaman allowed them to spread knowledge and motivate improved attitudes toward environmental health.